Burden of disease associated with asthma among the adult general population of five Middle Eastern countries: Results of the SNAPSHOT program. (June 2018) - Mungan, Dilsad; Aydin, Omur; Mahboub, Bassam; Albader, Mohammad; Tarraf, Hesham; Doble, Adam; Lahlou, Aaicha; Tariq, Luqman; Aziz, Fayaz; El Hasnaoui, Abdelkader
Abstract: Background: Asthma affects millions worldwide resulting in a significant disease burden. However, data on asthma burden from the Middle East is limited. This analysis describes the asthma burden in Egypt, Turkey and a Gulf cluster (Kuwait, Saudi Arabia and United Arab Emirates) as part of the SNAPSHOT program. Methods: SNAPSHOT was an observational, cross-sectional program carried out by telephone in a random sample of the adult general population of the five above mentioned countries. Quotas were defined per country demographics. Subjects were considered to have asthma if they fulfilled the screening criteria, based on the global Asthma Insights and Reality studies. Data collected included demographics, physician consultations, and asthma control (measured by the Asthma Control Test; ACT). Quality of life was assessed using the EuroQol Five-Dimension questionnaire (EQ-5D); and limitations to daily activities using the modified Sheehan Disability Scale (SDS). Results: 939 subjects answered questions related to asthma burden. Overall, 367 (44.2%) reported uncontrolled asthma (ACT≤19), and reported significantly lower EQ-5D-3L utility values (0.6 ± 0.4) and EQ-VAS scores (60.7 ± 24.2) compared to controlled subjects (0.8 ± 0.3 and 75.3 ± 19.8 respectively) ( p < 0.0001). A significantly higher proportion with uncontrolled asthma also reported experiencing impact on activities of daily living compared to subjects with controlled asthma ( p < 0.0001). Overall, 355 (37.8%) asthma subjects were followed by a physician. However, most visits were unscheduled (695;78.0%). Conclusion: Uncontrolled asthma imposes a significant burden in these Middle Eastern countries resulting in increased frequency of healthcare use, lower quality of life, and a higher impact on daily life compared to controlled asthma. Highlights: Asthma imposes a significant burden in the Middle East. Uncontrolled asthma was reported by 56% of asthma subjects in Egypt, 40% in Turkey and 38% in the Gulf Cluster. Only a third of asthma subjects were followed by a physician; most physician consultations (78%) were unscheduled. Uncontrolled asthma results in increased healthcare utilization. Subjects with asthma report a lower quality of life and a significant negative impact on performing daily activities.